Photochemical Processing of Inorganic and Organic Species in the Canadian High Arctic Aerosols: Impact of Ammonium Cation, Transition Metals, and Dicarboxylic Acids before and after Polar Sunrise at Alert - Dharmendra Kumar Singh (7484093); Kimitaka Kawamura (1770541); Pingqing Fu (1517941); Hideki Kasukabe (11347611); Ayako Yanase (4325674); Leonard A. Barrie (2371558) (2021)
Temporal variations and correlation statistics of major inorganic and organic species and carbonaceous components of the total suspended particulate matter (TSPM) at Alert were concurrently studied. Organic carbon (OC) and water-soluble organic carbon (WSOC) declined from February to mid-March together with elemental carbon (EC), but OC and WSOC increased in April while EC stayed low, suggesting photochemical production of organic aerosols. WSOC/OC ratios peaked in mid-April (89%). The ammonium availability index (AAI) increases from 31% (before sunrise) to 58% (after sunrise). Strong correlations of NH 4 + with WSOC and dicarboxylic acids (DCAs) were found, implying the formation of organic salts at polar sunrise. K + is substantially correlated ( R 2 = 0.96; p = 0.03) with levoglucosan before sunrise; however, the correlation decreases after. Significant correlations were found for 5 cations (NH 4 + , Na + , K + , Mg 2+ , and Ca 2+ ), 2-alkaline earth metals (Ca and Mg), and 3 transition metals (Fe, Cu, and Mn) with DCAs and WSOC during both periods. Fe and Cu are strongly correlated (up to R 2 = 0.80; p < 0.05) with DCAs before and after polar sunrise, implying the Fenton reaction both in dark and light periods. On the basis of the significant correlation, we found the plausibility of Fenton chemistry of Fe and Cu with oxalic acid. In the multiple linear regression model, Mn is the most significant predictor of WSOC followed by Cu and Fe after sunrise. This study demonstrates the importance of the photochemical processing of Arctic aerosols that are carried by long-range transport to the Arctic at Alert, and bridges and answers the research gap and some questions raised in our previous study (regarding, for example, the impacts of inorganic species, primarily NH 4 + and transition metals on organic aerosols).